US rocket with Russian engine gets to work. - Zak, A. (IEEE spectrum)
A new high-performance player has entered the crowded field of satellite launching with the inaugural flight in August 2002 of the Atlas-V rocket from Lockheed Martin Corp.'s brand new facility at Cape Canaveral, Fla. For its main propulsion system on the first stage, the Atlas-V boasts a Russian-built RD-180 engine-a modification of the RD-170, the worlds most powerful rocket engine, which powers the Russia's Zenit and giant Energia rockets. To carry more propellant, and hence more payload into orbit, the Atlas-V is much larger than its ancestors. Its first stage is taller and wider in diameter than those of its predecessors. Its upper stage consists of a Centaur rocket. The basic Atlas-V can boost 4950 kg of payload into a geostationary transfer orbit, used as a way station for most communications satellites on their way to final destinations over the equator.